2003
DOI: 10.1213/01.ane.0000086618.28845.9b
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in Chronic Pain Management: An Evidence-Based Review

Abstract: Ketamine has diverse effects that may be of relevance to chronic pain including: N-methyl-D-aspartic acid, alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, kainate, gamma-aminobutyric acid(A) receptors; inhibition of voltage gated Na(+) and K(+) channels and serotonin, dopamine re-uptake. Ketamine has been in clinical practice for over 30 yr; however, there has been little formal research on the effectiveness of ketamine for chronic pain management. In this review we evaluate the available clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0
29

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(223 citation statements)
references
References 45 publications
1
184
0
29
Order By: Relevance
“…However, as only one concentration of ketamine was employed, only a single dose was administered, and effects of ketamine were assessed at only one time point, further controlled studies are needed to determine whether the therapeutic effects of ketamine in CRPS are limited to dynamic allodynia and punctate hyperalgesia or also include other forms of hyperalgesia. Parenteral and oral forms of ketamine have shown some promise for treating the burning pain and exquisite skin hypersensitivity of CRPS and other chronic pain states associated with nerve injury [42]. However, administration by these routes is limited by central side effects such as hallucinations and nightmares.…”
Section: Discussionmentioning
confidence: 99%
“…However, as only one concentration of ketamine was employed, only a single dose was administered, and effects of ketamine were assessed at only one time point, further controlled studies are needed to determine whether the therapeutic effects of ketamine in CRPS are limited to dynamic allodynia and punctate hyperalgesia or also include other forms of hyperalgesia. Parenteral and oral forms of ketamine have shown some promise for treating the burning pain and exquisite skin hypersensitivity of CRPS and other chronic pain states associated with nerve injury [42]. However, administration by these routes is limited by central side effects such as hallucinations and nightmares.…”
Section: Discussionmentioning
confidence: 99%
“…131,132 At subanesthetic doses (100-150 µg/kg as initial bolus followed by a CRI of 60-120 µg•kg -1 •hr -1 ) it blocks NMDA receptors, thereby modulating central sensitization induced both by tissue damage. [133][134][135][136][137] Ketamine exhibits synergism with classical analgesics such as opioids, NSAIDs, local anesthetics and α 2 agonists; therefore it reduces opioid analgesic consumption and increases analgesic quality. [135][136][137] Ketamine is used primarily as an antihyperalgesic and anti-allodynic compound in human patients at risk of developing maladaptive pain after major tissue damage and not primarily as an analgesic agent per se.…”
Section: Ketaminementioning
confidence: 99%
“…55,75,76 Human studies have demonstrated the potential of the NMDA antagonist ketamine in the treatment of various chronic pain conditions, although with significant adverse effects. 77 Local spinal application of an NMDA receptor antagonist attenuated VZV-induced behavioral sensitization. 41 In PHN patient trials, however, some oral NMDA receptor antagonists have not proved beneficial.…”
Section: Preclinical Evaluationsmentioning
confidence: 99%